2021
DOI: 10.1159/000513341
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Curved Nail of the Fourth Toe with Subungual Hyperkeratosis

Abstract: Congenital curved nail of the fourth toe (CNFT) is a rare nail deformity. We report a case of CNFT with thickening and hyperkeratosis at the hyponychium and peripheral nail bed that was successfully treated using a novel surgical technique. A 7-year-old Japanese boy had a clawed nail with thickening and hyperkeratosis at the hyponychium and peripheral nail bed on his bilateral fourth toes. His chief complaint was pain. The nails of the bilateral fourth toes curved plantarly and exhibited thickening and hyperke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…To prevent the distal edge of the nail plate from growing into the skin and causing pain, it is recommended that the length of the nail plate be kept long enough to cover tip of the fourth toe. On the other hand, there have been reports of cases in which surgical treatment such as flattening of the nail bed has been performed for CNFT, and this may be considered in cases in which the curved nail plate grows into the skin and causes repeated pain 5,7 . However, as long as attention is paid on the occasion of nail clipping, there should be no major problem in daily life, suggesting that surgical intervention be considered as an exception.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To prevent the distal edge of the nail plate from growing into the skin and causing pain, it is recommended that the length of the nail plate be kept long enough to cover tip of the fourth toe. On the other hand, there have been reports of cases in which surgical treatment such as flattening of the nail bed has been performed for CNFT, and this may be considered in cases in which the curved nail plate grows into the skin and causes repeated pain 5,7 . However, as long as attention is paid on the occasion of nail clipping, there should be no major problem in daily life, suggesting that surgical intervention be considered as an exception.…”
Section: Discussionmentioning
confidence: 99%
“…Congenital curved nail of the fourth toe was first reported by Iwasawa et al in 1991, and interestingly, the majority of cases thus far reported in the English literature have been from Japan, with only one case from outside Asia. [1][2][3][4][5][6][7] A summary of the cases including ours is shown in Table 1. The majority of the cases were bilateral (15 out of 19), but four unilateral cases were also reported.…”
Section: Discussionmentioning
confidence: 99%